(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article offers methodological techniques for improving speech culture of students, improving their language communication. Deeper understanding of meaningful linguistic norms will help future specialists to make their speech not only correct, but also expressive, accurate, relevant. When considering the main aspects of speech activity the most common errors in the speech of students of Kazakh faculty are analyzed to investigate the reason of their occurrence. To solve this problem, the words are interpreted from different perspectives: meaning (monosemantic, polysemantic), expressive stylistic point of view (stylistically neutral, formal, literary, conversational and colloquial), obsolescence and novelty (archaisms, historicisms, neologisms), their origin (native Russian words Old Slavonic words, adoptions), field of use (general vocabulary, terminology, dialects, slang). Practical assignments that are offered will help students to understand the distinctive features of words: meaning, stylistic nuance, field of use, combinatory power.